The effectiveness of legal protection of the environment in reducing the damages of economic activities - NEKKACHE, Hamza (Journal of Human Sciences, 2020)
The industrial and technological progress that the world has witnessed since the beginning of the twentieth century - in addition to its positive results on human kind - has produced a set of negative consequences on many levels. Perhaps the most important of which is environmental degradation, as an inevitable consequence of industrial progress in all fields, although the interest of societies in its beginning is the race towards Progress, the idea of preserving the environment has entered the field of human interest in the recent period, especially in its legal field, considering that the deterioration of the environment affects the international community mainly in its existence, which led to the emergence of many conferences, ideas and legal texts in order to protect the environment. Algeria, like the rest of the world, has been covered by environmental awareness to keep up with environmental legislation in many legal texts aimed at protecting the environment.